A novel strategy for bioactive natural products targeting NLRP3 inflammasome in Alzheimer’s disease - Yang, Zhiyou; Liu, Junxin; Wei, Shuai; Deng, Jiahang; Feng, Xinyue; Liu, Shucheng; Liu, Mingxin (Frontiers in Pharmacology, 2023)
Alzheimer’s disease (AD), the most common type of dementia, is an ageing related progressing neurodegenerative brain disorder. Extracellular neuritic plaques composed of misfolded amyloid β (Aβ) proteins and intracellular neurofibrillary tangles formed by hyperphosphorylated tau protein are the two classical characteristics of AD. Aβ and tau pathologies induces neurite atrophy and neuronal apoptosis, leading to cognitive, language, and behavioral deficits. Although researchers have made great efforts for decades to explore the pathogens and therapeutics of AD, the intrinsic mechanism remains unclear and there are still no well-established strategies to restore or even prevent this disease. Thereby, it will be beneficial for the establishment of novel therapeutic strategy to figure out the intrinsic molecular mechanism interrelated with the initiation and progression of AD. Currently, a plethora of evidences indicate that neuroinflammation plays a crucial role in the pathogenesis of AD. Nucleotide-binding oligomerization domain (NOD)-like receptor pyrin domain-containing protein 3 (NLRP3) is a key inflammasome sensor of cellular stress and infection involved in the innate immune system. In response to a wide range of stimuli, such as Aβ, NLRP3 assembles apoptosis-associated speck-like protein (ASC) and procaspase-1 into an inflammasome complex to induce the caspase-1 mediated secretion of interleukin (IL)-1β/IL-18 in M1 polarized microglia, which triggers the pathophysiological changes and cognitive decline of AD. Thus, targeting NLRP3 inflammasome is likely to be an efficient way for AD treatment via regulating brain immune microenvironment. Furthermore, accumulating evidences have indicated that traditional Chinese medicine (TCM) exert beneficial effects on AD via NLRP3 inflammasome inactivation. In this review, we summarise the current reports on the role and activated mechanisms of the NLRP3 inflammasome in the pathogenesis of AD. We also review the natural products for attenuating neuroinflammation by targeting NLRP3 inflammasome activation, which provide useful clues to develop novel AD treatment strategies.